Analysis the Influence of Environmental, Social, and Governance (ESG) Disclosure, Earnings Management and Ceo Narcissm on Firm Value - Prayogo, Enny; Angela, Aurora; Natalia, Maria; Meiliu, Helen (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The primary goal in establishing a company is to achieve maximum profits, enchance shareholders’ wealth, and increase the value of the company. Paying attention to environmental, social and governance (ESG) issues is a critical component of maximing business value. In addition, another factor that is considered capable of influencing company value and is closely related to corporate governance is profit management practices. In terms of company management, the existence of CEO is thought to have the potential to influence a firm’s value in the eyes of investors. This study aims to examine the effects of environmental, social, and governance (ESG) disclosure, earnings management, and CEO narcissism on firm value. The research population consists of all public companies listed on the Indonesia Stock Exchange from 2019 to 2022. The research sample includes 42 public companies selected using the purposive sampling method. The data analysis method used multiple regression and testing the T and F hypotheses. The findings indicate that partially, ESG disclosure and CEO narcissism do not have a significant influence on firm value, while earnings management has a positive influence on firm value. However, simultaneously, ESG disclosure, earnings management and CEO narcissism have a significant influence on firm value.